Princess Academy - Hale, Shannon (New York : Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2007)
While attending a strict academy for potential princesses with the other girls from her mountain village, fourteen-year-old Miri discovers unexpected talents and connections to her homeland.
Newbery Medal/Honor
School Library Journal starred
Wilson's Junior High School
Booklist, June 2005
Bulletin (Center for Children's books), September 2005
Horn Book, April 2006
Keywords: Mountains -- Fiction; Princesses -- Fiction; Schools -- Fiction; Self-confidence -- Fiction; Telepathy -- Fiction; Mountains -- Fiction; Princesses -- Fiction; School stories; Self-confidence -- Fiction; Telepathy -- Fiction